PENGEMBANGAN BAHAN AJAR BERNUANSA ALAT MUSIK TRADISIONAL GAMELAN JAWA PADA MATERI LINGKARAN UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DENGAN MODEL PROBLEM BASED LEARNING - Rianda Sinaga; Hardi Tambunan; Firman Pangaribuan (LPPM Universitas Nias Raya, 2026)
This study aims to develop mathematics teaching materials incorporating the traditional Javanese gamelan cultural context in the topic of circles to improve students’ mathematical problem-solving skills through the Problem Based Learning (PBL) model. The research employed a Research and Development (R&D) approach using the ADDIE development model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects included eighth-grade junior high school students, mathematics teachers, and instructional design and content experts. Data were collected using expert validation sheets, teacher and student response questionnaires, classroom observation sheets, and mathematical problem-solving ability tests. The data were analyzed using qualitative and quantitative descriptive techniques, including N-Gain analysis to measure improvements in students’ problem-solving abilities. The results indicate that the developed teaching materials are valid and practical for classroom use. Furthermore, the implementation of gamelan-based teaching materials integrated with the PBL model was proven effective in enhancing students’ mathematical problem-solving skills in circle topics. The integration of local cultural contexts into mathematics learning increases student engagement, strengthens conceptual understanding, and creates meaningful and contextual learning experiences. Therefore, the developed teaching materials are suitable as an innovative alternative for mathematics instruction at the junior high school level.